Byzantium in Eastern European Visual Culture in the Late Middle Ages
1 online resource.
Keywords: Byzantium in Eastern European Visual Culture in the Late Middle Ages , edited by Maria Alessia Rossi and Alice Isabella Sullivan, engages with issues of cultural contact and patronage, as well as the transformation and appropriation of Byzantine artistic, theological, and political models, alongside local traditions, across Eastern Europe. The regions of the Balkan Peninsula, the Carpathian Mountains, and early modern Russia have been treated in scholarship within limited frameworks or excluded altogether from art historical conversations. This volume encourages different readings of the artistic landscapes of Eastern Europe during the late medieval period, highlighting the cultural and artistic productions of individual centers. These ought to be considered individually and as part of larger networks, thus revealing their shared heritage and indebtedness to artistic and cultural models adopted from elsewhere, and especially from Byzantium.